1996
DOI: 10.3168/jds.s0022-0302(96)76407-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Source and Amount of Dietary Protein on Milk Yield by Cows in Early Lactation

Abstract: The purpose of this research was to examine the effects of various amounts of CP and RUP on AA flow to the small intestine and milk yield of lactating dairy cows. The first trial was a 5 x 5 Latin square design using five ruminally and duodenally cannulated multiparous cows. Diets contained chopped alfalfa hay, corn silage, high moisture corn, solvent-extracted soybean meal, and specially processed soybean meal (60.2% RUP). Soybean meal replaced high moisture corn to increase dietary CP from 14.5 to 16.5 or 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
54
4
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 23 publications
17
54
4
4
Order By: Relevance
“…Pereira et al (2005), trabalhando com níveis crescentes de proteína bruta em vacas de leite mestiças (12,7 a 16,9% da matéria seca total da dieta), observaram efeito linear positivo dos níveis de proteína bruta sobre as digestibilidades da matéria seca, matéria orgânica, proteína bruta e fibra em detergente neutro. Vários autores relataram que a utilização de níveis crescentes de proteína bruta resultou em aumentos nas digestibilidades da matéria seca, matéria orgânica, proteína bruta e fibra em detergente ácido (Cunningham et al, 1996;Valadares et al, 1997;Broderick, 2003). Sniffen et al (1993) e Wilson & Kennedy (1996) afirmaram que a ingestão de compostos nitrogenados é importante para atender aos requerimentos microbianos, sobretudo daqueles agentes que digerem a fibra, resultando em aumento do consumo e do desaparecimento do alimento.…”
Section: Resultsunclassified
“…Pereira et al (2005), trabalhando com níveis crescentes de proteína bruta em vacas de leite mestiças (12,7 a 16,9% da matéria seca total da dieta), observaram efeito linear positivo dos níveis de proteína bruta sobre as digestibilidades da matéria seca, matéria orgânica, proteína bruta e fibra em detergente neutro. Vários autores relataram que a utilização de níveis crescentes de proteína bruta resultou em aumentos nas digestibilidades da matéria seca, matéria orgânica, proteína bruta e fibra em detergente ácido (Cunningham et al, 1996;Valadares et al, 1997;Broderick, 2003). Sniffen et al (1993) e Wilson & Kennedy (1996) afirmaram que a ingestão de compostos nitrogenados é importante para atender aos requerimentos microbianos, sobretudo daqueles agentes que digerem a fibra, resultando em aumento do consumo e do desaparecimento do alimento.…”
Section: Resultsunclassified
“…Three other studies conducted under circumstances similar to this study, but only during early lactation, have been reported (Christensen et al, 1993;Cunningham et al, 1996;Komaragiri and Erdman, 1997). In all cases, relatively high-producing Holstein cows were used, and corn silage, alfalfa, or both provided the forage.…”
Section: Dairy Cattlementioning
confidence: 99%
“…(1984). In contrast, the higher levels of BUN in cows fed diet B may have been due to reduced efficiency of nitrogen utilization in the rumen for a diet containing corn gluten meal compared to one containing distillers grains (Cunningham et al 1996;Ellison-Henson et al 1997). Previously, Wohlt et al (1991) found that cows fed diets supplemented with corn gluten meal excreted a greater proportion of absorbed N in the urine than cows fed soybean For personal use only.…”
mentioning
confidence: 99%